The sustainability of new programs and innovations: a review of the empirical literature and recommendations for future research - Wiltsey Stirman, Shannon (BioMed Central, 2012)
BACKGROUND: The introduction of evidence-based programs and practices into healthcare settings has been the subject of an increasing amount of research in recent years. While a number of studies have examined initial implementation efforts, less research has been conducted to determine what happens beyond that point. There is increasing recognition that the extent to which new programs are sustained is influenced by many different factors and that more needs to be known about just what these factors are and how they interact. To understand the current state of the research literature on sustainability, our team took stock of what is currently known in this area and identified areas in which further research would be particularly helpful. This paper reviews the methods that have been used, the types of outcomes that have been measured and reported, findings from studies that reported long-term implementation outcomes, and factors that have been identified as potential influences on the sustained use of new practices, programs, or interventions. We conclude with recommendations and considerations for future research. METHODS: Two coders identified 125 studies on sustainability that met eligibility criteria. An initial coding scheme was developed based on constructs identified in previous literature on implementation. Additional codes were generated deductively. Related constructs among factors were identified by consensus and collapsed under the general categories. Studies that described the extent to which programs or innovations were sustained were also categorized and summarized. RESULTS: Although "sustainability" was the term most commonly used in the literature to refer to what happened after initial implementation, not all the studies that were reviewed actually presented working definitions of the term. Most study designs were retrospective and naturalistic. Approximately half of the studies relied on self-reports to assess sustainability or elements that influence sustainability. Approximately half employed quantitative methodologies, and the remainder employed qualitative or mixed methodologies. Few studies that investigated sustainability outcomes employed rigorous methods of evaluation (e.g., objective evaluation, judgement of implementation quality or fidelity). Among those that did, a small number reported full sustainment or high fidelity. Very little research has examined the extent, nature, or impact of adaptations to the interventions or programs once implemented. Influences on sustainability included organizational context, capacity, processes, and factors related to the new program or practice themselves. CONCLUSIONS: Clearer definitions and research that is guided by the conceptual literature on sustainability are critical to the development of the research in the area. Further efforts to characterize the phenomenon and the factors that influence it will enhance the quality of future research. Careful consideration must also be given to interactions among influences at multiple levels, as well as issues such as fidelity, modification, and changes in implementation over time. While prospective and experimental designs are needed, there is also an important role for qualitative research in efforts to understand the phenomenon, refine hypotheses, and develop strategies to promote sustainment.